Impact of ICT on Adopting Online Education at Higher Education in Nepal: A Factual Analysis - Kunwar, Rajendra (Education and Development, 2020)
This article primarily concerns the impact of ICT in adopting online education in higher education in Nepal. It focuses on the baseline information about the impact of ICT on higher education. This study has adopted a narrative literature review with a descriptive-analytic method to reveal the salient features associated with the impact of ICT in higher education. The study has adopted a rigorous interpretative process and synthesized the impact of ICT on adopting online education. The utilization of ICT in education is enforcing teachers as well as educational institutions to review pedagogical practices. No matter, the issue of use of ICT has been raised in the whole educational system; and similarly, there are also the issues related to equality in access to education and the delivery of quality education for the learner due to the lack of policy provisions, infrastructure and competencies of the teacher and the student. Thus, the increasing trends of utilizing ICT have been enforcing to transform the structure of education system as well as educational pedagogy.